An examination of the benefits of incorporating aspects of play therapy, speech and language therapy and physiotherapy into the classroom for children with Autism Spectrum Disorder to enhance their educational experience. - Cronin, Alanna (STER, 2024)
This dissertation seeks to examine how the implementation of elements of play therapy, speech and language therapy (SLT) and physiotherapy into the classroom of children with Autism Spectrum Disorder (ASD) can enhance their educational experience. The objectives of this dissertation are to research ASD, define it and examine research from the foundations of the discovery of the disorder to the present-day research. Research has shown that children with ASD can have deficits in social skills, communications skills, and movement skills. Secondly, to explore play therapy and explore the benefits of using aspects of play therapy with children with ASD. This dissertation will explore how effective the implementation of play therapy is when used in the classroom with children with ASD. Following this, this research will explore physiotherapy and explore the benefits of using aspects of physiotherapy with children with ASD. This dissertation will explore how effective the implementation of physiotherapy is when used in the classroom with children with ASD. Lastly, this dissertation will explore speech and language therapy and the benefits of using aspects of it in the classroom with children with ASD. This dissertation will then study how effective the implementation of speech and language therapy is when used in the classroom with children with ASD. Overall, this study aims to investigate the effect of different interventions on various needs of students with ASD. This article is a snapshot of a broader dissertation, which examined the benefits of implementing these interventions by looking on a global scale of interventions in Australia as well as the United States and then looks to Ireland to recommend how we can best include these interventions into our inclusive practice.
Keywords: Child Centered Play Therapy; Speech and Language Therapy; Physiotherapy in Education; Autism; Autistic children--Education; Play therapy; Physical therapy; Education--Ireland